2014
DOI: 10.1186/1471-2261-14-29
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of valve composition to elucidate the role of collagen in aortic valve calcification

Abstract: BackgroundExtracellular matrix (ECM) disarray is found in calcific aortic valvular disease (CAVD), yet much remains to be learned about the role of individual ECM components in valvular interstitial cell (VIC) function and dysfunction. Previous clinical analyses have shown that calcification is associated with decreased collagen content, while previous in vitro work has suggested that the presence of collagen attenuates the responsiveness of VICs to pro-calcific stimuli. The current study uses whole leaflet cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 34 publications
4
47
0
Order By: Relevance
“…Altogether, our study indicates that mineralization of collagen at both fiber and fibril levels reduces their intrinsic flexibility, which is an asset in bones. However, this is a drawback in arteries and other soft tissues, where excessive stiffness reduces the functionality of the tissue and leads to a range of disorders (19,20). Appreciable concentrations of calcium, phosphorus, silicium, and sulfur in the calcified lesions of spherical forms have been reported previously (51,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, our study indicates that mineralization of collagen at both fiber and fibril levels reduces their intrinsic flexibility, which is an asset in bones. However, this is a drawback in arteries and other soft tissues, where excessive stiffness reduces the functionality of the tissue and leads to a range of disorders (19,20). Appreciable concentrations of calcium, phosphorus, silicium, and sulfur in the calcified lesions of spherical forms have been reported previously (51,62).…”
Section: Discussionmentioning
confidence: 99%
“…A typical feature of age-related diseases is the ectopic mineralization of ECM. This abnormal mineralization reduces the structural integrity and elasticity of arteries, which impairs cardiovascular function (19,20). Moreover, alterations in the mechanisms of calcium and phosphorous homeostasis are responsible for both skeletal and vascular disorders (21).…”
mentioning
confidence: 99%
“…As the extracellular matrix contents, particularly collagen, are determinants for maintaining valve integrity and mechanical strength,20 26 non-enzymatic collagen crosslinks (AGEs) induce a decreased valve extensibility with an increased valve stiffness 2 6 21. Both AGEs and calcium deposits have been detected on the extracellular aortic heart valve sites 19.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental studies have reported that aortic valve calcification is an active collagen-dependent regulated mechanism integral to aortic stenosis 20 28. Furthermore, AGEs could enhance the affinity of extracellular matrix components for calcium by the receptor of advanced glycation end products pathway 27 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation